Optimal PSA density threshold for prostate biopsy in benign prostatic obstruction patients with elevated PSA levels but negative MRI findings - Yiji Peng; Chengcheng Wei; Ying Li; Fuhan Zhao; Yuan Liu; Tao Jiang; Zhipeng Chen; Jun Zheng; Jiong Fu; Peng Wang; Wenhao Shen (BMC Urology)
Abstract Purpose This study was designed to identify a useful clinical parameter or model for prostate biopsy in surgery-indicated benign prostate hyperplasia (BPH) patients with elevated PSA levels and negative multiparametric prostate magnetic resonance imaging (MRI) results. Patients and methods We retrospectively analyzed clinical and pathological data from patients who were diagnosed with BPH and admitted to the inpatient department for surgery between January 2010 and September 2020. Clinical data, including age, prostate specific antigen (PSA) level, F/T PSA ratio, prostate volume, and PSA density (PSAD), were used for comprehensive analysis. Univariate and multivariate logistic regression analyses were performed to develop a predictive model. Receiver operating characteristic (ROC) analysis and decision curve analysis (DCA) were performed to assess the diagnostic value of the predictive model, PSA concentration, F/T PSA ratio and PSAD. Results A total of 318 patients were included in the study, 8.2% (26/318) of whom were histologically diagnosed with prostate cancer (PCa). Univariate and multivariate logistic regression analyses revealed that PSAD was the only independent predictor of PCa biopsy. ROC curve analysis of PCa detection revealed a larger area under the curve (AUC) for the predictive model (AUC 0.855) and for PSAD (AUC 0.848) than for PSA (AUC 0.722) or the F/T PSA ratio (AUC 0.635). DCA demonstrated that the optimal strategy would be to restrict biopsies to men with a PSAD of 0.30 ng/ml/cm3. Conclusions Our study suggested that for BPH patients with surgical indications who present with PSA abnormalities and negative imaging findings, the use of a new PSAD threshold of 0.30 ng/ml/cm3 could facilitate convenient and sound biopsy decisions. This approach could reduce the complications and length of hospital stay associated with biopsies and reduce hospital costs.